Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/adfm.202110637
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Based Single Molecule Force Sensor For Characterization of α5β1 Integrin Tension Required for Invadopodia Formation and Maturation in Cancer Cells

Abstract: Invadopodia are involved in cancer invasion by generating mechanical forces and secreting proteolytic enzymes. It is hypothesized that physical forces applied to integrin, especially α 5 β 1 integrin, are strongly associated with the generation of invadopodial forces and protrusive activity of invadopodia; however, their mechanical relationship remains elusive. Here, a new deoxyribonucleic acid-based force probe is developed for mapping α 5 β 1 integrin tension with single-molecule precision. Using this probe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In addition to the TGT ruptures, in all tested conditions, punctate fluorescent signal loss under cells (named “ventral rupture”) was observed. This might be caused by DNase recruited in invadopodia or invadopodia activity in the MDA-MB-231 cells ( Pal et al, 2021 ; Kim et al, 2022 ). For the MCF7 cells, the ventral rupture was rarely found; instead, the edge rupture was dominant in all conditions ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the TGT ruptures, in all tested conditions, punctate fluorescent signal loss under cells (named “ventral rupture”) was observed. This might be caused by DNase recruited in invadopodia or invadopodia activity in the MDA-MB-231 cells ( Pal et al, 2021 ; Kim et al, 2022 ). For the MCF7 cells, the ventral rupture was rarely found; instead, the edge rupture was dominant in all conditions ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kim et al developed a novel TGT probe based on an ATN-16 ligand for specific binding to a 5 b 1 integrin. 99 As seen in Fig. 5a, a force tolerance of 43 pN or 54 pN can be controlled by the location of biotins on the bottom DNA strand, while T tol of 4100 pN was estimated by disassociation of the biotin-streptavidin bond.…”
Section: Dna-based Mtfmmentioning
confidence: 99%
“…To modulate the specific force delivered by the integrins, a tension gauge tether (TGT) was prepared using an oligonucleotide ( Wang and Ha, 2013 ). The TGT method has shown that the adhesion and invadopodia maturation of metastatic cancer cells necessitate the presence of a particular integrin type, namely, α5β1 integrin, along with integrin tension exceeding 40pN ( Kim et al, 2022 ). Furthermore, a micro-confinement TGT (µC-TGT) has been developed to comprehend alterations in integrin-mediated force during cell migration and adhesion within restricted microchannels.…”
Section: Cancer Progression In Hypoxic Tumor-microenvironmentmentioning
confidence: 99%